2021
DOI: 10.3390/rs13132619
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Effectiveness of Active Learning: Introducing Artificial Data Generation in Active Learning for Land Use/Land Cover Classification

Abstract: In remote sensing, Active Learning (AL) has become an important technique to collect informative ground truth data “on-demand” for supervised classification tasks. Despite its effectiveness, it is still significantly reliant on user interaction, which makes it both expensive and time consuming to implement. Most of the current literature focuses on the optimization of AL by modifying the selection criteria and the classifiers used. Although improvements in these areas will result in more effective data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…In addition, the resulting classifcation performance of AL-trained classifers is frequently inconsistent and marginally improves the classifcation performance when compared to classifers trained over the entire training set. In addition, there is also signifcant variability in the data selection efciency during diferent runs of the AL iterative process [20].…”
Section: Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the resulting classifcation performance of AL-trained classifers is frequently inconsistent and marginally improves the classifcation performance when compared to classifers trained over the entire training set. In addition, there is also signifcant variability in the data selection efciency during diferent runs of the AL iterative process [20].…”
Section: Proposed Methodsmentioning
confidence: 99%
“…(2) Generalization of the generator module proposed in [20] from oversampling techniques to any other data augmentation mechanism and/or policy.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in contexts of limited data availability (i.e., small datasets), deep learning approaches are not appropriate since the amount of parameters to be tuned during the learning phase often exceeds the number of observations in the dataset, making it overparametrized. The augmentation of small datasets using heuristic approaches is explored in an Active Learning context in [30]. The authors found that significantly smaller amounts of curated data using Active Learning, along with heuristic data augmentation methods, achieved a classification performance comparable to classifiers trained over the full dataset.…”
Section: Heuristic Approachesmentioning
confidence: 99%